INCREASING THE MEASUREMENT OF SOIL WATER CONTENT WITH THE CHARACTERIZATION OF MAGNETIC FIELD INDUCTION SENSORS USING MODEL EQUATIONS FOR THE INTERNET OF THING APPLICATION - Perdana, Doan; Darmawan, Dudi; Ismardi, Abrar; Agung Enriko, I Ketut; Fathona, Indra Wahyudhin; Cahyono, Ongko (Journal of Applied Engineering Science, 2022)
This study proposes an increase in the measurement of soil water content with sensor characterization that can be integrated with the internet of things. The main contribution of this work is the improvement in measurement accuracy compared to measurements using a moisture meter. This is achieved through an electromagnetic approach using a pair of transceiver coils as a sensor. Determination of water content in the soil is carried out through the formulation of an equation model that connects the measured voltage on the receiving coil with the mass of water contained. It is known that the use of the equation model in the test data results in better accuracy with an error of 2.03% - 17.43%, compared to measurements using a moisture measuring device with an error of 13.21% - 32%. This equation model that uses the electromagnetic method provides an alternative solution for determining the soil water for wider land use so that can be used for internet of things application.